2017
DOI: 10.5603/mrj.2017.0002
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and anxiety symptoms among patients with inflammatory bowel diseases

Abstract: Depressive and anxiety symptoms among patients with inflammatory bowel diseases ABSTRACT Introduction. This study was conducted on a population of patients with inflammatory bowel disease (IBD) and was based on an assessment of the prevalence and severity of depression and anxiety symptoms in various clinical aspects. The psychological features of IBD patients are very important in the perception of symptoms, but crucial as triggers of IBD or as a releasing factor for IBD symptoms recurrence.Methods. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 108 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The literature suggests that excess body weight is highly-associated with the appearance of anxiety and depression symptoms (41,42) . A recent study in Poland with patients with IBD also found significant results regarding overweight and higher levels of depressive symptoms (43) . Finally, it is necessary to point some limitations of the present study.…”
Section: Discussionmentioning
confidence: 95%
“…The literature suggests that excess body weight is highly-associated with the appearance of anxiety and depression symptoms (41,42) . A recent study in Poland with patients with IBD also found significant results regarding overweight and higher levels of depressive symptoms (43) . Finally, it is necessary to point some limitations of the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Epidemiological studies have established that anxiety and depression are the most prevalent psychiatric disorders among IBD patients [ 10 13 ]. Also patients suffering from other immune-mediated inflammatory diseases, such as multiple sclerosis or rheumatoid arthitis, are at the increased risk of psychiatric comorbidity [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differences between men and women with IBD has been reported several times [ 33 , 34 ]. In our study, girls perceived more pain at diagnosis and worst flare than boys.…”
Section: Discussionmentioning
confidence: 99%